Fuel Consumption in Ukraine: Evidence from Vector Error Correction Model - Oliskevych, Marianna; Beregova, Galyna; Tokarchuk, Viktor (International Journal of Energy Economics and Policy, 2018)
This paper aims to investigate the problems of energy market in Ukrainian economy. The empirical research of various energy sources in Ukraine showed the existence of significant relationships between coal, gas, diesel fuel, gasoline and oil consumption. We estimated the vector error correction model that combined evaluation of long-term interrelations between different fuels indexes and the dynamic description of their short-term behaviour. The modelling showed that in the long-run there were two equilibrium relationships that determined the dynamics of fuel consumption in Ukraine. We estimated the adjustment speeds and described the correlation between short-run changes in fuel usage and deviations from long-run equilibrium. The gas consumption was the most valuable kind of energy that had a great impact on functioning of Ukrainian energy market and the whole economy. The diversification of energy consumption types can give an opportunity to improve the economic situation. Keywords: energy market, fuel consumption, vector autoregressive model. JEL Classifications: O13, Ð¡ 32.